NARRATING VIOLENCE AND POWER: AN EXPLORATION OF SOCIAL AND FAMILIAL DYNAMICS IN ANNA BURNS’ LITTLE CONSTRUCTIONS - Dr. Arun Kumar (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2024)
This paper explores the intricate interplay of violence and power within social and familial dynamics as portrayed in Little Constructions, the lesser-known but thematically rich novel by Anna Burns. Set in an unnamed town steeped in a violent culture, the narrative navigates a world where the boundaries between public and private power are blurred. Through a fractured, non-linear storytelling style, Burns delves into the oppressive forces that shape individual and collective behavior, revealing the pervasive influence of patriarchal structures, familial control, and community-sanctioned violence. At the heart of the novel is the Doe family, whose members are both victims and agents of violence, entangled in complex power relations within their immediate family and the broader society. This study examines how Burns depicts the family as a microcosm of larger social mechanisms, with violence becoming a tool of control, survival, and rebellion. The novel’s unique narrative style reflects the chaotic and fragmented experience of those living under constant threat, creating a disorienting, yet deeply resonant depiction of power’s insidious nature. By focusing on Burns’ exploration of gender dynamics, trauma, and the cyclical nature of violence, this paper aims to analyze how the novel critiques societal norms and familial expectations. It also considers how the narrative structure itself reinforces themes of control and disempowerment, ultimately providing a commentary on the ways in which violence pervades both intimate and public spheres. Through this examination, Little Constructions is positioned not only as a profound commentary on personal and collective trauma but also as a broader reflection on the ways violence and power sustains oppressive social orders.